ANALISA HUBUNGAN KOMUNIKASI VERBAL DAN NON VERBAL PERAWAT DENGAN TINGKAT KEPUASAN PASIEN DI RUANG PERAWATAN BEDAH - Rahmayanti, Yeni Nur (Jurnal Stethoscope, 2025)
Verbal communication is a type of communication carried out by nurses directly or indirectly to patients while non-verbal communication is a type of communication carried out by nurses with non-verbal cues such as facial expressions, expressions, smiles and others. Patients are often dissatisfied with the quality and amount of information received from health workers. Thirty-five to forty percent of patients are dissatisfied with communicating with doctors and nurses, the aspect that makes them most dissatisfied is the amount and type of information received. The amount of information given by doctors to patients is an average of 18 types of information to remember, in fact they are only able to remember 31%. More than 60% of those interviewed after meeting with doctors and nurses misunderstood the instructions given to them. This is caused by the failure of health professionals to provide complete information, the use of medical terms (difficult to understand) and the many instructions that must be memorized by patients. The research design used is cross sectional which is analytic in nature. The independent variable is the nurse's verbal and non-verbal communication, while the dependent variable in this study is the level of patient satisfaction. This study used stratified random sampling or simple random sampling which is a type of probability samples or random samples. The samples were taken from patients who were sick and treated in surgical treatment rooms as many as 38 people. Based on the results of the above study, it can be seen that of the 38 patients in the Surgical Treatment Room, the majority of patients said the nurses' verbal and non-verbal communication was good. There is a relationship between verbal and non-verbal communication with the level of patient satisfaction being treated.